Phenotyping determination of cyp1a2 enzyme activity using caffeine in sheep - Kamil Uney; Bünyamin Tras (Eurasian Journal of Veterinary Sciences)
Aim: The aims of this study were to determine the validity of the plasma metabolic ratios (MR) to investigate the CYP1A2 activity in practice and to compare in vivo CYP1A2 enzyme activity using caffeine (CF) as a probe in Morkaraman (MK), Akkaraman (AK) and Anatolia Merino (AM) sheep breeds. Materials and Methods: Caffeine was administered as a single dose of 5 mg/kg b.w. by the intravenous in MK, AK and AM sheep breeds. The plasma levels of CF and paraxanthine (PX) were measured using high-performance liquid chromatography. CYP1A2 phenotyping was measured using the ratio [(PX/CF)AUC] between areas under the plasma concentration-time curve (AUCs) of PX and CF and the ratios [(PX/CF)MR→3-16 h] between plasma concentrations of PX and CF at 3 to 16 h after CF administration. Correlations between the plasma (PX/CF)MR→3-16 h and (PX/CF)AUC ratios were determined to investigate of the CYP1A2 phenotyping by single blood sampling in practice. Results: It was determined that the more reliable sampling time within the plasma (PX/CF)MR→3-16 h ratios in the determination of the CYP1A2 phenotyping was 10 h after CF administration. (PX/CF)MR→10 h and (PX/CF)AUC ratios were similar (p>0.05) among sheep breeds. Conclusion: The plasma (PX/CF)MR→10 h ratio might be used as a rapid and simple screening test for CYP1A2 phenotyping in sheep. CYP1A2 enzyme may not be clinically important in the observed differences to the effects of drugs and environmental chemicals with its substrates among MK, AK and AM sheep breeds.